Sleep as a Target for Optimized Response to Smoking Cessation Treatment. Issue 2 (23rd October 2017) - Patterson, Freda; Grandner, Michael A; Malone, Susan K; Rizzo, Albert; Davey, Adam; Edwards, David G
Abstract: : Declining national rates of current tobacco use to an all-time low of 15.1% represents a public health victory. Undermining this progress, however, are smoking rates of up to 50% among high-risk, low-income populations. Current FDA-approved treatments for nicotine dependence are ineffective with between 70–95% of treatment-seekers relapsing within the first year of attempted abstinence. Thus, identification of novel intervention targets to optimize response to currently available treatments for nicotine dependence is a critical next step. One such target may be sleep insomnia. Insomnia is a clinically verified nicotine withdrawal symptom but, to date, addressing insomnia or other sleep disturbance symptoms as an adjunctive smoking cessation therapy has yet to be fully considered. To this end, this manuscript presents a narrative review of: (1) sleep continuity and architecture in smokers versus nonsmokers; (2) effects of nicotine abstinence on sleep; (3) possible mechanisms linking sleep with smoking cessation outcomes; (4) plausible adjunctive sleep therapies to promote smoking cessation; (5) possible treatments for unhealthy sleep in smokers; and (6) directions for future research. Taken together, this will provide conceptual support for sleep therapy as an adjunctive treatment for smoking cessation. Implications: This narrative literature review presents a comprehensive discussion of the relationship between habitual sleep and cigarette smoking. The extent to which unhealthy sleep in smokers may be a viable intervention target for promoting response to smoking cessation treatment is considered. Ultimately, this review provides conceptual support for sleep therapy as an adjunctive treatment for smoking cessation.